Funkcje prawa wyborczego w kontekście wyborów do Parlamentu Europejskiego - Langer, Wojciech (Polityka i Społeczeństwo, 2021)
The text contains a catalog of the functions of electoral law (creating, expressing the will of the voters, legitimizing, controlling and integrating) and a brief description of their character. Then, the European Parliament is described, focusing on regulations concerning the election procedure, both on a European and national level. The next part presents an evaluation of each function’s implementation, through the norms of electoral law to the European Parliament, particularly in the context of the elections of the 25th May 2014 from the Subcarpathia district, especially on the basis of the elec-tion’s results, stated in the declaration of the State Election Commission of the 26th May 2014.